The Undergraduate Diploma in Horticultural and Floricultural Production of the Faculty of Agricultural and Forestry Sciences of the National University of La Plata, Argentina. Assumptions, dilemmas and challenges emerging from the training experience - Garat, Juan José (2022)
The Undergraduate Diploma in Horticultural and Floricultural Production was created in 2018 at the National University of La Plata (UNLP) to generate a training space for horticultural and floricultural producers in the region. Thus was born an initiative that seeks to incorporate into the university educational system those people who, without having a secondary degree, are trained according to their needs and interests. With the premise of approaching the teaching-learning process from a Freirian perspective and counting on a teaching body integrated almost entirely by teachers from the Faculty of Agricultural and Forestry Sciences (UNLP), the first cohort was developed in 2019. his first experience was carried out through a series of meetings to involve the recipients to optimize the production system, discuss practices and management for horticultural and floricultural production and discuss some practices of the dominant model. The result has been acceptable, although reflection on the experience generates questions and answers about the objectives, methodology, actors (mainly producers and teachers), and types of intervention in a productive and socioeconomic context like the current one.